The effectiveness of English as a general course program in Yogyakarta State University - Jamilah, - (JOURNAL OF EDUCATION, 2015)
This study was aimed at ï¬ nding out the effectiveness of English as a general course program in Yogyakara State University using a survey technique. The population covered students, teachers, and program managers. Respondents from  students were selected by the cluster random sampling technique while respondents from teachers and program managers were purposively selected. Data were collected using questionnaires, interview guides, and documents, and were descriptively analyzed. Findings showed that English as a general course program in Yogyakarta State University was ineffective since there were a lack of management support and teacher's support, no coordination among the parties involved, no sound curriculum to guide the teachers in implementing the program, a lack of teaching staff development, and low work satisfaction among the teachers and students